Sound Exchange Between The Consonants In “Al Kamil” On Language And Literature In The Light Of Modern Linguistics - Hayder Jasim Lafta Al-Saedi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study deals with the description and analysis of the sound exchange between consonants issues, in the examples contained in Al Kamil book on language and literature for the grammarian Abu Abbas Al-Mubarrad , and its interpretation from the perspective of modern language, which is perceived from a modern point of view, seeking to interpreting it scientifically, and subject them to what was produced by the modern science of language sound laws, which explained the changes in the sound structure of these words that characterized many of the old Arabic language books as anomaly and strange as well as other descriptions that indicate these words articulation of steady and often and a lot, which are considered the characteristics that old Arab scholars invoked them in the production of normative acts, that straightened the right linguistic behavior later and ruled the linguistic absentmindedness. The study was committed in its consideration of these issues in the descriptive interpretative approach that was adopted by modern language school, which describes the linguistic phenomenon, and does not stop there, but also to analyze, interpret and explain the reasons identified in that phenomenon about a certain linguistic behavior and no other, and engaged in some of its parts in the comparative approach and clarification.